RTP1 encodes a novel endoplasmic reticulum (ER)‐localized protein in Arabidopsis and negatively regulates resistance against biotrophic pathogens. Issue 4 (20th October 2015) - Pan, Qiaona; Cui, Beimi; Deng, Fengyan; Quan, Junli; Loake, Gary J.; Shan, Weixing
Summary: Oomycete pathogens cause serious damage to a wide spectrum of plants. Although host pathogen recognition via pathogen effectors and cognate plant resistance proteins is well established, the genetic basis of host factors that mediate plant susceptibility to oomycete pathogens is relatively unexplored. Here, we report on RTP1, a nodulin‐related MtN21 family gene in Arabidopsis that mediates susceptibility to Phytophthora parasitica . RTP1 was identified by screening a T‐DNA insertion mutant population and encoded an endoplasmic reticulum (ER)‐localized protein. Overexpression of RTP1 rendered Arabidopsis more susceptible, whereas RNA silencing of RTP1 led to enhanced resistance to P. parasitica . Moreover, an RTP1 mutant, rtp1‐1, displayed localized cell death, increased reactive oxygen species (ROS) production and accelerated PR1 expression, compared to the wild‐type Col‐0, in response to P. parasitica infection. rtp1‐1 showed a similar disease response to the bacterial pathogen Pseudomonas syringae pv. tomato ( Pst ) DC3000, including increased disease resistance, cell death and ROS production. Furthermore, rpt1‐1 exhibited resistance to the fungal pathogen Golovinomyces cichoracearum, but not to the necrotrophic pathogen Botrytis cinerea . Taken together, these results suggest that RTP1 negatively regulates plant resistance to biotrophic pathogens, possibly by regulating ROS production, cell death progression and PR1 expression.